Implementation of Non-Profit Entity Accounting (PSAK 45) at the Istiqomah Foundation - Fitri Dwi Jayanti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the application of Financial Accounting Standards Statement 45 on Financial Reporting of Non-Profit Entities at the Istiqomah Foundation, which operates in the education sector. Non-profit organizations, especially educational foundations, require an accountable financial reporting system to maintain stakeholder trust. The purpose of this study is to analyze the conformity of the Istiqomah Foundation's accounting practices with PSAK 45 standards and to identify obstacles encountered in its implementation. The research method uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results show that the Istiqomah Foundation has prepared a statement of financial position and activity report, but there are still deficiencies in the presentation of the cash flow statement and notes to the financial statements. The classification of net assets is not fully in accordance with the provisions of PSAK 45, which distinguishes between permanently restricted, temporarily restricted, and unrestricted net assets. The main obstacles found include limited human resources who understand non-profit accounting and the absence of an adequate computerized accounting system. The study recommends the need for non-profit accounting training for foundation financial managers and the development of an accounting information system that is appropriate to the characteristics of non-profit educational entities.